PENGARUH LITERASI KEUANGAN DAN GAYA HIDUP TERHADAP MINAT MAHASISWA MENGGUNAKAN PAYLATER (STUDI PADA MAHASISWA UNIVERSITAS MUHAMMADIYAH SORONG) - Haiqal, Muhammad Rifqy; Bintari , Wisang Candra; Hidayah, Nurul (ANALISIS, 2024)
This research aims to find out whether financial literacy and Lifestye influence students' tendency to use Paylater. The independent variables in this research are financial literacy (X1) and lifestyle (X2), and the dependent variable in this research is interest in using Paylater (Y). This research uses a quantitative approach using descriptive and correlation methods. The sample in this study was taken using non-probability techniques with the Quota Sampling technique. The respondents used in this research were 264 Muhammadiyah Sorong University students who were drawn using the quota sampling technique. The research results show that the independent variables of financial literacy and lifestyle variables have a simultaneous and partial effect on the dependent variable Student interest in using Paylater.